ANALISIS DAN STRATEGI BUDI DAYA MAGGOT DALAM PENGELOLAAN SAMPAH ORGANIK - Ruhmawati, Tati; Wahyudin, Uyu; Saripah, Iip; Sudiapermana, Elih; Suryadi, Ace; Robandi, Babang; Hasanah, Viena Rusmiati; Komar, Zaenal; Rosita, Neng Ayu (Poltekkes Kemenkes Bandung, 2024)
Sustainable waste management is a responsibility for consumption and production, by the Sustainable Development Goals (SDGs). According to data from the Karawang Regency Central Statistics Agency, in 2021, it is estimated that the amount of organic waste produced every day in the Village X area will range from 16.13 to 18.43 tonnes. This high amount of organic waste is a major problem regarding the region's environmental cleanliness and health. People at Village X Waste Bank are trying to utilise organic waste as food for fly larvae (maggots), but the success rate has only reached 30%. Research in Village X in October 2023 aims to determine the problems faced and strategies for optimizing maggot cultivation. The sample consisted of three informants, namely Village X, the director of Waste Bank X, and Village X staff. The research was conducted using a descriptive method with a qualitative approach, and the analysis technique for strategy formulation was Fishbone Diagram analysis. Based on the analysis, the factors causing problems at Bank Sampah X include: lack of knowledge and training, obsolete machines and unsupportive funds, lack of facilities and infrastructure, inappropriate waste characteristics, lack of communication and monitoring, lack of role of local youth organizations, presence of maggot predators, and lack of role of local youth organizations. Monitoring and evaluation activities are strategies to overcome these problems.